Functions

Oct 2019
42
1
united states
Hello I am having trouble with this question.
For
f(x) = x2 + 6x + 5, evaluate f(x + 2) − f(x).
Simplify.
I tried of substituted x with x+2 and after add the equation to the result in negative form gives me 2x+9, was incorrect. I don't know what I doing wrong?. Could someone help me please.
 

romsek

MHF Helper
Nov 2013
6,725
3,030
California
$f(x) = x^2 + 6x + 5$

$f(x+2) = (x+2)^2 +6(x+2) + 5 = \\
x^2 + 4x+4 +6x+12 + 5 = \\
x^2 + 10x + 21$

$f(x+2)-f(x) = (x^2+10x+21) - (x^2 + 6x+5) = \\
4x + 16$
 
Oct 2019
42
1
united states
Ohh, I understand now. Thanks romsek